The Effect Of Using The K-Pop Idol Ambassador Brand And Company Brand Image On Purchase Decisions On The Marketplace Shopee - Era Friyda Kumala; Joko Widodo; Mukhamad Zulianto (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the effect of the use of K-Pop Idol Brand Ambassadors and Company Brand Image on Purchase Decisions on the Shopee Marketplace for Class 10-11 Social Studies Students at SMA Negeri 4 Probolinggo and to determine the most influential variables among Kpop idol brand ambassadors and the company's brand image on purchasing decisions on the Shopee marketplace for students in grades 10-11 majoring in social studies at SMA Negeri 4 Probolinggo. In the sampling technique using Non Probability Sampling as many as 71 respondents, the data analysis used in this study was multiple linear regression analysis. The results showed that the magnitude of the influence of Kpop idol brand ambassadors and the company's brand image on purchasing decisions at the Shopee Marketplace for Class 10-11 Social Studies students at SMA Negeri 4 Probolinggo was 80.3% while the remaining 19.7% was influenced by the independent variables. not investigated in this study. This shows that the Kpop idol brand ambassador variable has more influence on purchasing decisions compared to brand image.